Morfologia do primeiro estágio juvenil de quatro espécies de caranguejos Leucosioidea (Crustacea: Decapoda: Brachyura), com proposta de padronização para as descrições dos estágios iniciais em Decapoda - Degani, Eduardo [UNESP] (2014)
Morphology of the initial stages of crustacean life cycle is very important to the establishment of their ecological, taxonomical and phylogenetic relationships. This study describes the morphology of the first juvenile stage of Persephona liechtensteinii, P. mediterranea, P. punctata and Ebalia stimpsoni. Larvae on the megalopa stage were obtained from the neuston of Ubatuba, SP, and reared individually in laboratory until they reached a size that allowed the correct identification of their species. Afterwards, exuvia from the first juvenile were dissected under stereomicroscope and drawings and measurements, under optical microscope, equiped with camara lucida. Some of the morphological differences observed were: marginal plumose setae on the telson of P. liechtensteinii with simple setae on the surface; absence of setae on the base of the antenna in P. punctata; a simple seta on the protopod of the maxillule of E. stimpsoni; a plumose seta on the endopod of the maxilla in P. mediterranea; a simple seta on the coxal endite of the maxilla in P. punctata; 2 simple seta on the epipod of the 3rd maxilliped in P. liechtensteinii; different types of setae on the exopod of the 3rd maxilliped: 8 spatulate in P. mediterranea, 9-10 plumodenticulate in P. punctata, 23-25 simple on the surface and 28-29 marginal long plumose in P. liechtensteinii, and 7 small simple in E. stimpsoni. The shared characters between these species were: a rounded carapace with small granules equally sparse and, with the exception of E. stimpsoni, 3 granulous spines on the posterior margin